On the Metaphysics of Experimental Physics - Rogers, K. author. aut Link
VII, 252 p.
Keywords: This provocative and critical work addresses the question of why scientific realists and positivists consider experimental physics to be a natural and empirical science. Taking insights from contemporary science studies, continental philosophy, and the history of physics, this book describes and analyses the metaphysical presuppositions that underwrite the technological use of experimental apparatus and instruments to explore, model, and understand nature. By revealing this metaphysical foundation, the author questions whether experimental physics is a natural and empirical science at all.